2008
DOI: 10.1096/fj.08-113142
|View full text |Cite
|
Sign up to set email alerts
|

Both lipid environment and pH are critical for determining physiological solution structure of 3‐D‐conserved epitopes of the HIV‐1 gp41‐MPER peptide P1

Abstract: In terms of background, the solution structure of monomeric peptide P1 (residues 649-683), located in the conserved membrane proximal region (MPER) of HIV-1 envelope glycoprotein gp41, is first reported here in dodecylphosphocholine (DPC) micelles. P1 is the minimal MPER region that permits interaction with the mucosal galactosyl ceramide HIV-receptor; it also contains epitopes recognized by major gp41-specific, broadly neutralizing immunoglobulin Gs (IgGs), 2F5 and 4E10, determinant in HIV fusion/infection. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 64 publications
3
41
1
Order By: Relevance
“…However, more defined secondary structures have been described for some shorter peptides (D 664 -K 683 ) both in solution and in micelle-or liposomebound states in infrared (17,26,30) and CD spectroscopic studies (16). More recently, nuclear magnetic resonance spectroscopic studies of micelle-bound peptides corresponding to E 662 -K 683 (31) and S 649 -K 683 (8) revealed that the C-terminal half of MPER consists of two shorter helices separated by a short hinge and that the N-terminal half of MPER is mostly disordered.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, more defined secondary structures have been described for some shorter peptides (D 664 -K 683 ) both in solution and in micelle-or liposomebound states in infrared (17,26,30) and CD spectroscopic studies (16). More recently, nuclear magnetic resonance spectroscopic studies of micelle-bound peptides corresponding to E 662 -K 683 (31) and S 649 -K 683 (8) revealed that the C-terminal half of MPER consists of two shorter helices separated by a short hinge and that the N-terminal half of MPER is mostly disordered.…”
Section: Resultsmentioning
confidence: 99%
“…MPER peptide anchorage on the membrane surface facilitates efficient 2F5 and 4E10 binding. Recent studies that have described the binding of MAbs 2F5 and 4E10 to MPER peptides on liposomes used either no membrane anchor (31) or a lipidic anchor (8) and relied on the inherent membrane affinity of the MPER peptides. The importance of membrane anchoring on peptide orientation and the effect on MAb binding have not been studied.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The short peptides were either solubilized in detergent micelles (39,44,45) or in bound forms cocrystallized with MPER-recognizing antibodies (31,32). Of the trimeric structures, one was not membrane-associated and does not bind 2F5 or 4E10 antibodies (38), and the other was part of a six-helix bundle representing the postfusion state of gp41 (13).…”
Section: Discussionmentioning
confidence: 99%
“…2-4A). Structures of shorter or even longer peptides show spots of partial structuring as 3 10 -and ␣-helix (33,35,73,(75)(76)(77), but none of them display continuous helical structures for the sequence spanning the full 2F5 epitope plus the downstream aromatic rich sequence preceding the TMD anchor (Fig. 1).…”
Section: Wfnitnwlwyikmentioning
confidence: 99%